Juridical Analysis of Inheritance Handling for Heirs with Mental Disabilities - Raja V. Situmorang, Primus; Hayati, Mulida; Prama Wulandari, Vicka (Dinasti Research, 2025)
This study aims to analyze juridically how the civil law system in Indonesia, especially the Civil Code (KUH Percivil), regulates and protects inheritance rights for heirs who experience mental disorders. The type of research chosen is normative legal research with a legislative approach and a conceptual approach. In the context of inheritance distribution, problems arise when one of the heirs is incompetent due to a psychiatric condition, so his rights are often ignored or even used by other heirs. One of the case studies analyzed was the handling of inheritance and legal capacity in a family where an heir is mentally disturbed. This study found that the distribution of inheritances without involving or appointing legal representatives for heirs who are not legally competent is legally flawed and can be canceled. Therefore, the appointment of curators by the court is an important mechanism in ensuring justice and legal protection for those who experience mental disorders. This study recommends the need to increase legal understanding among the public and law enforcement officials regarding the importance of guardianship in the inheritance distribution process, as well as strengthening legal protection for people with mental disorders as part of the principle of equality before the law.